PROBLEM-BASED LEARNING (PBL): CAN IMPROVE HIGHER-ORDER THINKING SKILLS (HOTS) OF PROSPECTIVE ELEMENTARY SCHOOL TEACHER STUDENTS? - Darmawan, Nurani Hadnistia; Hilmawan, Hilman (PrimaryEdu : Journal of Primary Education, 2021)
Mastery of 21st-century skills is one of the goals in learning activities. One of the factors to consider is that the teacher must have HOTS as the spearhead of learning. This study aims to improve HOTS, namely critical thinking skills and creative thinking of prospective elementary school teacher students through PBL. This study uses a pre-experimental method with a one-group pre-test-post-test design. The research instrument used was a description test of 15 items. The sample of this research is 30 students of STKIP Bina Mutiara Sukabumi PGSD Study Program. The results showed that the HOTS of prospective elementary school teacher students at STKIP Bina Mutiara Sukabumi increased by using PBL. The t-test results obtained were 0.00 < Î± = 0.05, indicating that this learning model significantly influences students' HOTS. The gain test results obtained an n-gain value of 0.34, which indicates that the increase in student HOTS is in the "medium" category. The details of the results of each HOTS aspect during the post-test were in the "good" category, namely fluency, flexibility, originality, and evaluation. Aspects of elementary clarification, basic support, inference, advanced clarification, strategy and tactics, are in the "enough" category. The last HOTS aspect, namely elaboration, is in the "less" category.